Detection of Medical Errors in Kidney Transplantation: A Pilot Study Comparing Proactive Clinician Debriefings to a Hospital-Wide Incident Reporting System - McElroy, Lisa M. (Surgery, 2014)
BACKGROUND: Rates of medical errors and adverse events remain high for kidney transplant patients, who are particularly vulnerable due to the complexity of their disease and the kidney transplant procedure. Although institutional incident reporting systems are utilized in hospitals around the country, they often fail to capture a substantial proportion of medical errors. The goal of this study was to assess the ability of a proactive, web-based clinician safety debriefing to augment the information about medical errors and adverse events obtained via traditional incident reporting systems. METHODS: Debriefings were sent to all individuals listed on operating room personnel reports for kidney transplantation surgeries between April 2010 and April 2011 and incident reports were collected for the same time period. The World Health Organization International Classification for Patient Safety was used to classify all issues reported. RESULTS: A total of 270 debriefings reported 334 patient safety issues (179 safety incidents, 155 contributing factors), and 57 incident reports reported 92 patient safety issues (56 safety incidents, 36 contributing factors). Compared to incident reports, more attending physicians completed the debriefings (32.0 vs. 3.5%). DISCUSSION: The use of a proactive, web-based debriefing to augment an incident reporting system in assessing safety risks in kidney transplantation demonstrated increased information, more perspectives of a single safety issue, and increased breadth of participants.